Identification Identification of Functional Groups in Sludge 120C of Ammonia IB Factory PT Petrokimia Gresik by ATR-FTIR Method - Vidya Nur Cholillah (Unesa Journal of Chemistry, 2025)
The ammonia production process uses natural gas and nitrogen as raw materials with the main product being ammonia and by-product CO2. CO2 in the ammonia production process must be removed by absorption using a benfield solution and converting CO2 to CH4. Unit 144D of PT Petrokimia Gresik IB ammonia plant is poisoned by CO2 gas from the LTS (Low Temperature Shift) unit. The indication is based on the formation of deposits in the 120C cone strainer unit and it is suspected that the deposits are ammonium carbamate or ammonium carbonate. Identification was carried out using the ATR-FTIR method by comparing the sample with standard ammonium carbamate as well as with the IR spectra of ammonium carbonate and ammonium bicarbonate from the literature. The results showed that the similarity of the sample with ammonium carbamate was 87.6%. There are peaks at wave numbers 3500-3300 cm-1 showing N-H vibrations of primary amines, 1600-1700 cm-1 which shows C=O stretching vibrations. Then at 1490-1410 cm-1 which shows the presence of carbonate ions (CO32-). The wave number between 1450-1400 cm-1 shows the vibration of NH4+ ions. It is likely that the compound formed is a mixture of ammonium carbamate and ammonium carbonate because testing was not carried out to obtain the percentage of similarity of ammonium carbonate with the sample directly.